Application of a novel solid superbase catalyst of Na2O/molecular sieve analogs (HND-63) in synthesis of plant-based monoglyceride and its catalytic mechanism - Keying Jing; Yaping Lv; Fanfan Song; Shangde Sun (Grain & Oil Science and Technology)
Monoglyceride (MAG) is a widely used nonionic surfactant. In this work, an economic and green solid superbase HND-63 was utilized to synthesize monoglyceride, and the independent variables were examined to achieve the highest MAG content. HND-63 was characterized in order to explore the potential reasons for its high MAG selectivity. At the same time, the catalytic mechanism of HND-63 in glycerolysis reaction was also focused on in this paper. A maximum of 72.50 % MAG content was obtained under the optimal reaction parameters (reaction temperature of 110.5 °C, reaction time of 209 min, molar ratio of glycerol to oil of 9.2:1, and catalyst dosage of 10.1 %). The activation energy Ea and the pre-exponential factor A of the reaction were 61.37 kJ/mol and 6.33 × 106 mol·L−1·min−1, respectively. The basic site of HND-63 is O2−, which is loaded on molecular sieve analogs in the form of Na2O, thus providing great convenience for recovery. The findings offer a novel solid superbase that could be potentially applied to glycerolysis reactions, providing the foundation for further development of plant-based surfactants.